Development and testing of a continuous mixing plant for pot mixture - ANI S. T; Er. Joby Bastian (Guide) (Tavanur 1997 Department of Farm Power Machinery and Energy)
Development and testing of a continuous mixing plant for pot mixture
Development and testing of a continuous mixing plant for pot mixture